2022
DOI: 10.3390/jcm11113187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Third and Fourth mRNA-Based Booster Vaccinations on SARS-CoV-2 Neutralizing Antibody Titer Formation, Risk Factors for Non-Response, and Outcome after SARS-CoV-2 Omicron Breakthrough Infections in Patients on Chronic Hemodialysis: A Prospective Multicenter Cohort Study

Abstract: The aim of this study is to determine the effect of repeated vaccinations on neutralizing SARS-CoV-2 IgG antibody titers, evaluate risk factors for immunological non-response, and to report breakthrough infections in chronic hemodialysis patients. Methods: A prospective, multi-center cohort study in 163 chronic hemodialysis patients was conducted. Antibody titers were measured three months after second, third, and fourth (10 pts) booster vaccinations. SARS-CoV-2 neutralizing antibody titers in BAU/mL and % inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Several studies report of superior immunity after initial mRNA-1273 prime/boost vaccination when compared to BNT162b2 in haemodialyis patients (30,31) or in the general population (32)(33)(34) and further improved humoral responses after triple vaccination in dialysis patients (35)(36)(37)(38)(39). Third dose vaccination with mRNA-1273 or BNT162b2 provided comparable protection against symptomatic SARS-CoV-2 infection in the general population, although differences between both vaccines were observed after the second dose (40).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report of superior immunity after initial mRNA-1273 prime/boost vaccination when compared to BNT162b2 in haemodialyis patients (30,31) or in the general population (32)(33)(34) and further improved humoral responses after triple vaccination in dialysis patients (35)(36)(37)(38)(39). Third dose vaccination with mRNA-1273 or BNT162b2 provided comparable protection against symptomatic SARS-CoV-2 infection in the general population, although differences between both vaccines were observed after the second dose (40).…”
Section: Discussionmentioning
confidence: 99%
“…Despite good public knowledge and awareness about COVID-19 severity and vaccine safety [ 22 ], hesitancy or refusal to take the vaccine has been present among a large portion of Egyptian citizens, even medical students [ 23 ] and healthcare workers [ 24 , 25 ]. Patients on maintenance HD have been shown to have diminished and waning humoral responses after COVID-19 vaccination [ 26 ], which improved after a third [ 27 ] or a fourth booster dose [ 28 ]. For Egyptian patients on maintenance HD, a previous study showed that about 40% of patients were hesitant or resistant to taking the COVID-19 vaccine [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report of superior immunity after initial mRNA-1273 prime/boost vaccination when compared to BNT162b2 in haemodialyis patients (28,29) or in the general population (30)(31)(32) and further improved humoral responses after triple vaccination in dialysis patients (33)(34)(35)(36)(37). Third dose vaccination with mRNA-1273 or BNT162b2 vaccines provided comparable protection against symptomatic SARS-CoV-2 infection in the general population although differences between both vaccines were observed after the second dose (38).…”
Section: Discussionmentioning
confidence: 99%